(3JCdja aj NUGFU GdRhGjG hGdOhGFQs
(3ChdgG (B:s
(3hCeG GdHQLd agh bWYJG eYOf ObjbJGf eJUdJGf EJUGdkG eYVdjkG s
(3BNQgG (B:s
(3NdGUI gPG GdaUd (B: (3jfbSe GdeKdK HGdfSHI dRhGjGg Edi KdGKI CbSGe (B: (3bGFe GdRhGjI , hMGO GdRhGjI , hefaQL GdRhGjI , RHGdfSHI dCVdGYg Je GdLRA GdChd , hjdjg GdLRA GdKGfi ai bjGS GdSdWhM hGdGLSGe s
(3jTJed Ydi CTcGd gfOSjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3MGdI GdfSNI LjOI s
Keywords: (3GdcjejGA h GdWHjYjGJs